Watercolor unleashed new directions for traditional painting techniques - Pollard, Julie Gilbert 1947- (North Light Books, an imprint of F+W Media, Inc., 2013)
"'Watercolor Unleashed' from Julie Gilbert Pollard will show you how to expand your watercolor painting skills an approach watercolor in new ways. Learn great traditional watercolor painting techniques as well as tips for achieving a loose, painterly quality. Simple, forgiving techniques means fewer mistakes and more fun results. Practice each technique and learn how to paint a landscape along the way. This great watercolor painting book combines representational painting styles with abstract painting techniques and studies. Give yourself more freedom on your palette with these exceptional watercolor landscapes & abstract painting techniques"--The publisher.